อิทธิพลของแรงจูงใจและการรับรู้ของนักท่องเที่ยวชาวตะวันตกที่ส่งผลต่อ ความพึงพอใจในการมาท่องเที่ยววัดในกรุงเทพมหานคร : กรณีศึกษา วัดพระศรีรัตนศาสดาราม วัดพระเชตุพนวิมลมังคลาราม และวัดอรุณราชวราราม - แสงสี ณัทกร (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2017)
The aims of this research are to study the influence of motivations as push factors, pull factors and the perception affected the satisfaction of the four hundreds Western tourists. According to the results, most of the sample respondents are female aged between 18-30 years old. The education levels are higher than bachelor degree, worked as a high-level professional careers, the average annual income less than US 20,000, came from Europe, especially from Spain. Most of them planned trips by themselves, traveled with friends, came to Thailand for the first time and stayed in Thailand for 15-21 days. The motivations as push factors were prestige, relaxing, to see novelty and to learn the history and culture, respectively. The motivations also as pull factor were architecture and needs to be well-known. The perceptions of the Western tourists can be ranked as crowded of tourists, interpretation, image, facilities, sacred atmosphere, and the expense of entrance fee, respectively. The result of Multiple Regression analysis revealed 6 factors affecting their satisfaction. These factors were to see novelty, architecture, need to be well-known, image, facilities and sacred atmosphere.